The state’s precautionary intervention in compensating for bodily damages resulting from unsecured traffic accidents - Chouiter, Imen Ratiba (Journal of Human Sciences, 2021)
Legal problems generated by traffic accidents have been extensively addressed by legal experts who have noted in particular the difficulties experienced by victims in obtaining compensation, especially in the event that the Insurer invokes a case of forfeiture or of exclusion. This prompted the legislator to approach the issue of compensation and civil liability for accidents from an innovative approach by incidentally intervening by the State through the automobile guarantee fund.